Social Protection in Pakistan : Managing Household Risks and Vulnerability - World Bank (Washington, DC, 2012)
The report is the result of an inter-institutional collaborative effort between the Government of Pakistan, civil society, and international donors. This report finds that while Pakistan implements a wide array of social protection programs, the effectiveness of these programs could be significantly improved. The report finds that social protection programs in Pakistan face important constraints in terms of coverage, targeting, and implementation, and inability to respond to vulnerability, which will need to be overcome in order that they can more effectively protect the poor. The report suggests a two-pronged approach for social protection reform: (i) improving the ability of safety net programs to reach the poor, promote exit from poverty, and respond to natural disasters; coupled with (ii) a longer term approach for strengthening social security. Considering social protection as a system rather than a collection of different programs would allow the government to curtail fragmentation, improve the quality of social protection spending, and have higher impact. Given fiscal constraints, the report suggests that coverage expansion first exploits the opportunity for efficiency improvements in current programs, through better targeting and reduction in duplication and overlap. However, the decline in real spending on the two main safety net programs is worrisome. It is therefore welcome that the government is considering how best to ensure adequate yet fiscally affordable spending on safety nets as part of its draft social protection strategy.